Pilot study comparing the quality of airway seal in an endotracheal tube with a viscoelastic cuff compared to standard endotracheal tubes - Pedro Alejandro Bravo Fernández; Daniel A Cuevas Nieves; Nieves Leon-Gomez; Juan Jose Artazkoz del Toro; Ricardo Martinez-Ruiz (Multidisciplinary Respiratory Medicine, 2026)
Background: Inadequate endotracheal tube (ETT) cuff sealing permits microaspiration of subglottic secretions, driving ventilator-associated pneumonia and perioperative respiratory complications. Standard cylindrical and tapered cuffs remain susceptible to microchannel formation and leakage. This pilot study evaluated a novel ETT with a 90-mm self-expanding viscoelastic cuff (V-Cuff®) operating at ambient pressure compared to standard and specialty ETTs in vitro. Methods: Five ETTs of each type—standard cylindrical (Ruschelit®), specialty tapered (Shiley Evac/TaperGuard®), and V-Cuff®—were tested at 37°C in a 3D-printed tracheal model with 5 cmH₂O positive end-expiratory pressure (PEEP). Evaluations included upper and lower pressure threshold assessments (UPTA and LPTA) and simulated swallowing (80 mmHg, 2s) and coughing (125 mmHg, 3s). Continuous and categorical outcomes were analyzed using Mann-Whitney U and Fisher's Exact tests, respectively. Results: Under 5 cmH₂O PEEP, the standard ETT leaked immediately at 0 mmHg on UPTA. Both specialty and V-Cuff® ETTs tolerated supracuff pressures >90 mmHg on UPTA (p90 mmHg (p=0.008 vs. standard and specialty). During simulated swallowing and coughing, all standard and specialty ETTs leaked (5/5), while the V-Cuff® maintained complete seal integrity without leakage (0/5; p=0.008). Conclusions: In this pilot in vitro study, the V-Cuff® ETT demonstrated superior airway sealing under all static and dynamic conditions compared to standard and tapered-cuff ETTs. These preliminary findings suggest the improved seal may reduce tracheal soiling, though prospective clinical validation is required to confirm reductions in aspiration-related complications.